Aplikasi Pengelolaan Tadarus Al-Quran Online dengan Kombinasi Media Sosial WA-Bisnis dan Email - Joko Troyono; Prita Haryani; Irmah Gisfas (Program Studi Sistem Informasi, 2020)
Pandemic does need for information technology very extraordinary. This era forces all fields to inevitably use information technology, starting from working from home, school from home, teaching from home, selling from home, meetings must be from home, even almost all work and activities have been done from home. Social media is most-liked as a means of communicating data and information, even though the use of social media for data communication transactions is like we provide data to a social media server, and that data can be used by other parties. In social media that we usually do is we can easily paste the URL from other news, then the social media display will appear short news from its. Even in e-mail, we usually receive a web - form emails, there is a URL that is used to make transactions to the intended object. The results of this study obtained a combination of several technologies, including social media WhatsApp, email, YouTube and web applications to improve data exchange in transactions and dissemination of information so that all activities undertaken can be managed and analysed. Keywords: Applications, Pandemic, Social media, Web